SURGERY: TEXTBOOK FOR STUDENTS OF HIGHER MEDICAL EDUCATIONAL INSTITUTIONS - BEREZNYTSKYY, Yakiv; SULYMA, Volodymyr (The Eurasia Proceedings of Educational and Social Sciences, 2017)
At the same time, the fact is obvious that if these capabilities are not peculiar to everyone but only to some doctors, it becomes an indicator not for mass professional thinking but personal qualities of a definite person. Broad medical activity, which includes a significant amount of both patients and medical personnel, frequency of main diseases (socially significant in many respects) and requirements on rendering high quality medical care demand mass training of clinical thinking. First of all, it is demanded by the training of the diagnosis recognition process. How is the training performed now? Nowadays, the nosological principle of training dominates. A student studies one or another disease using textbooks and lectures. Thus, the student learns symptoms of the given disease in general, without relation to one or another concrete patient. Later at a lecture, a teacher presents a patient with the disease under study to the group of students, explains specific symptoms using patient’s example and checks how students acquired the particular nosological form. Thereby conclusions are made about a young doctor’s ability to recognize diseases and to treat patients who have the given disease. Both teachers and students are sure that a fund of knowledge about many diseases is formed in this way and the doctor will be able to do his job professionally by accumulation of this knowledge.